2019
DOI: 10.1523/jneurosci.0940-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Two Compasses in the Central Complex of the Locust Brain

Abstract: Many migratory insects rely on a celestial compass for spatial orientation. Several features of the daytime sky, all generated by the sun, can be exploited for navigation. Two of these are the position of the sun and the pattern of polarized skylight. Neurons of the central complex (CX), a group of neuropils in the central brain of insects, have been shown to encode sky compass cues. In desert locusts, the CX holds a topographic, compass-like representation of the plane of polarized light (E-vector) presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 58 publications
8
47
0
Order By: Relevance
“…These data support our initial observation of clusters of glomeruli with similar tunings and PSI values (Fig. 8B,C), contrasting with the polarotopic organization of tunings across the PB found for CPU1 neurons in locusts (likely homologous to P-F-R neurons in flies) (Heinze and Homberg, 2007;Honkanen et al, 2019;Pegel et al, 2019). A limited representation of two orthogonal angles of polarization in columnar neurons would also be congruent with a single predominant tuning being conveyed by the R4m population (Fig.…”
Section: E-pg Neurons Respond To Polarized Light With Flexible Tuningsupporting
confidence: 86%
See 1 more Smart Citation
“…These data support our initial observation of clusters of glomeruli with similar tunings and PSI values (Fig. 8B,C), contrasting with the polarotopic organization of tunings across the PB found for CPU1 neurons in locusts (likely homologous to P-F-R neurons in flies) (Heinze and Homberg, 2007;Honkanen et al, 2019;Pegel et al, 2019). A limited representation of two orthogonal angles of polarization in columnar neurons would also be congruent with a single predominant tuning being conveyed by the R4m population (Fig.…”
Section: E-pg Neurons Respond To Polarized Light With Flexible Tuningsupporting
confidence: 86%
“…Across animals, we found no common relationship between glomerulus position in the PB and the preferred angle of polarization (AoP) of E-PG neurons (Fig. 8H), matching the findings for the homologous CL1a neurons in locusts (Heinze and Homberg, 2009;Pegel et al, 2019). We then asked whether, on the timescale of a single stimulus cycle (30 s), there was any relationship between PB position and preferred AoP in an individual animal.…”
Section: E-pg Neurons Respond To Polarized Light With Flexible Tuningsupporting
confidence: 74%
“…In many insects, sensory input to the CX is largely visual, and response properties often have a clear navigational context. Strong responsiveness has been found to the angle of polarized light from dorsal directions in field crickets, desert locusts, monarch butterflies, dung beetles and sweet bees (Vitzthum et al, 2002;Sakura et al, 2008;Heinze and Reppert, 2011;el Jundi et al, 2015;Stone et al, 2017), approaching dark objects and small moving targets in locusts (Rosner and Homberg, 2013;Homberg, 2015b, 2017), wide-field motion in cockroaches, flies and bees (Kathman et al, 2014;Weir et al, 2014;Weir and Dickinson, 2015;Stone et al, 2017), and azimuth-dependent presentation of light spots or vertical bars in flies, beetles, cockroaches, monarch butterflies and desert locusts (Heinze and Reppert, 2011;el Jundi et al, 2015;Jayaraman, 2013, 2015;Turner-Evans et al, 2017;Varga and Ritzmann, 2016;Weir and Dickinson, 2015;Pegel et al, 2018Pegel et al, , 2019. In flies, visual responsiveness of certain CX neurons depends on the animal's behavioral state (Seelig and Jayaraman, 2013;Weir and Dickinson, 2015;Turner-Evans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, a picture of which population of neurons codes for which kind of stimuli and to what extent responsiveness depends on a particular behavioral context is just beginning to emerge. One of the best understood networks of neurons within the locust CX encodes heading direction relative to sky compass signals (Pfeiffer and Homberg, 2014;el Jundi et al, 2015;Bockhorst and Homberg, 2015a;Pegel et al, 2018Pegel et al, , 2019. Blue, cloudless sky shows a pattern of polarized light, which is used by many insects for spatial orientation (Horváth and Varjú, 2004;Horváth, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, the CX is of key importance for the computations required to derive a heading 21 signal [2,6,[11][12][13][14]. In locusts (Schistocerca gregaria), intracellular recordings have revealed a 22 neuronal layout that topographically maps the animal's orientation relative to simulated skylight 23 cues, including polarized light and point sources of light [15][16][17]. Calcium imaging of columnar 24 neurons connecting the EB and the PB (E-PG neurons) in the fruit fly Drosophila melanogaster, 25 revealed that the E-PG neuronal ensemble maintains localised spiking activity -commonly called 26 an activity 'bump' -that moves from one group of neurons to the next as the animal rotates 27 with respect to its surrounding [18,19].…”
mentioning
confidence: 99%